The other Catholics : remaking America's largest religion - Byrne, Julie, 1968- (New York : Columbia University Press, 2016)
Independent Catholics are not formally connected to the pope in Rome. They practice apostolic succession, seven sacraments, and devotion to the saints. But without a pope, they can change quickly and experiment freely. Some affirm communion for the divorced, women's ordination, clerical marriage, and same-sex marriage. From their early-modern origins in the Netherlands to their contemporary proliferation in the United States, these #x93;other Catholics" represent an unusually liberal, mobile, and creative version of America's largest religion. In The Other Catholics, Julie Byrne shares the remarka.
Other Catholics -- Catholic. Weeping and woo-woo : observing independent Catholicism in America -- Succession. Mission and metamorphosis : narrating modern Catholic history ; Love and meta-Catholicism : founding the Church of Antioch -- Sacraments and saints. Dance and balance : leading American independents ; Mix and mysticism : experimenting with US Catholicism ; Sacraments and saints : hearing a new call -- All Catholics.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 050
Keywords: Catholic Church -- United States -- History -- 21st century; Catholic Church; Catholic Church; Independent Catholic churches -- United States; RELIGION / Christianity / Protestant; Independent Catholic churches; United States; 2000-2099; Electronic books; History